Alkyl Chain Regiochemistry of Benzotriazole‐Based Donor Polymers Influencing Morphology and Performances of Non‐Fullerene Organic Solar Cells. Issue 11 (10th January 2018) - Chen, Shangshang; Zhang, Lin; Ma, Chao; Meng, Dong; Zhang, Jianquan; Zhang, Guangye; Li, Zhengke; Chow, Philip C. Y.; Ma, Wei; Wang, Zhaohui; Wong, Kam Sing; Ade, Harald; et al.
Abstract: The effects of alkyl chain regiochemistry on the properties of donor polymers and performances of non‐fullerene organic solar cells are investigated. Two donor polymers (PfBTAZ and PfBTAZS) are compared that have nearly identical chemical structures except for the regiochemistry of alkyl chains. The optical properties and crystallinity of two polymers are nearly identical yet the PfBTAZ:O‐IDTBR blend exhibits nearly double domain size compared to the blend based on PfBTAZS:O‐IDTBR. To reveal the origins of the very different domain size of two blends, the morphology of neat polymer films is characterized, and it is found that PfBTAZ tends to aggregate into much larger polymer fibers without the presence of O‐IDTBR. This indicates that it is not the polymer:O‐IDTBR interactions but the intrinsic aggregation properties of two polymers that determine the morphology features of neat and blend films. The stronger aggregation tendency of PfBTAZ could be explained by its more co‐planar geometry of the polymer backbone arising from the different alkyl chain regiochemistry. Combined with the similar trend observed in another set of donor polymers (PTFB‐P and PTFB‐PS), the results provide an important understanding of the structure–property relationships that could guide the development of donor polymers for non‐fullerene organic solar cells. Abstract : The effects of alkyl chain regiochemistry on the properties of donor polymers and the performance of non‐fullerene organic solar cells are investigated. It is found that the alkyl chain regiochemistry has great impacts on the morphology features of the neat and blend films, and the PfBTAZS:O‐IDTBR‐based cells with small domain size can achieve a high efficiency of 10.4%.